Anthropometry and physical performance of Estonian top-level female volleyball players - Stamm, M.; Stamm, R.; Aasorg, M.; João, P. V. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Morphological characteristics are considered essential to achieve top-level performance in volleyball (Malousaris et.al., 2008). The objective of this study was to examine the physical and anthropometric characteristics of Estonian top-level female volleyball players and to find if there is a relationship between physical fitness tests and competition results. Methods: For this purpose, we studied 52 female volleyball players who belonged to the six best teams of Estonia; their age was 20.8 ± 4.2 years. The physical fitness tests included two jump tests, an endurance test, a speed test and a medicine ball throwing test. The anthropometric examination included 10 measurements: height, weight, lower chest circumference, waist circumference, hip circumference, upper and lower leg circumference, arm circumference, flexed and tensed arm circumference, wrist circumference. Results: The endurance test correlated statistically significantly and negatively with body measurements - smaller players had greater endurance. For purposes of analysis, volleyball players` somatotype was established by physical anthropometry. It was possible to distinguish between players in different positions by their somatotypes in a 5 SD height-weight classification. Tempo players belonged to the big or the leptomorphous class, libero players belonged to the small or the pycnomorphous class, and setters were more often leptomorphous or small. Opposite players and outside attackers varied greatly and had different somatotypes. Discussion: The physical fitness test results were also placed in the 5SD classification of weight and height. The classification showed that jumping ability and speed test results improved gradually from the small to the medium to the big class: leptomorphous players could jump higher than pycnomorphous ones. These results can suggest some indicators for selection volleyball players for different positions. We also verified that teams who had better results in physical fitness tests also got better places in Estonian championships.